Pediatrics : (McGraw-Hill Professional, 2004)
Everything a resident or clinician needs-to-know about pediatric medicine in a concise bulleted format. Written by a preeminent team of clinicians from the top children’s hospitals in the country, this quick-reference and board review is organized according to the clinical issues tested on the Board of Pediatrics Examination.